2003
DOI: 10.1038/sj.gt.3301956
|View full text |Cite
|
Sign up to set email alerts
|

Potent antitumor activity of IL-13 cytotoxin in human pancreatic tumors engineered to express IL-13 receptor α2 chain in vivo

Abstract: Interleukin-13 receptor (IL-13R) a2 chain plays a key role in ligand binding and internalization. We have recently demonstrated that this cytokine receptor chain has unique characteristics in tumor biology: it inhibits tumorigenicity of breast and pancreatic cancer in animal models. In this study, we have exploited IL-13Ra2 chain and established a novel approach for pancreatic cancer therapy. For this, a plasmid encoding the IL-13Ra2 chain gene was mixed with liposomes and injected into subcutaneously or ortho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…Recently, there has been growing interest in localized cancer therapy where toxicity to healthy tissues needs to be minimized [40][41][42]. Implantation of transduced MOs at the constantly changing tumor site may provide a preferred carrier to deliver specific genes for localized cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there has been growing interest in localized cancer therapy where toxicity to healthy tissues needs to be minimized [40][41][42]. Implantation of transduced MOs at the constantly changing tumor site may provide a preferred carrier to deliver specific genes for localized cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work implicates IL-13 as an important autocrine factor for several tumors, [25][26][27][28] and the expression of IL-13Ra2 represents an important biomarker for several solid malignancies. [29][30][31][32][33] However, little is known about the role of IL-13 in CTCL, apart from the finding that both CTCL tumor cell lines 56 and SS malignant cells produce IL-13 in vitro. 18 Although it is well established that CTCL disease progression is associated with Th2 skewing of the cytokine profile and increasing immunosuppression, 18 the role of IL-13 as a regulator of tumor-cell proliferation has never been addressed.…”
Section: Discussionmentioning
confidence: 99%
“…21,23 Several studies implicate IL-13 as an autocrine factor for several tumors that express IL-13Ra1, the signaling receptor for IL-13, 24 including Hodgkin lymphoma, 25,26 B-CLL, 27 and breast carcinoma. 28 A variety of other human cancer cells such as those derived from glioma, 29,30 squamous cell carcinoma of head and neck, 31 pancreatic cancer, 32 and breast cancer 33 overexpress IL-13Ra2, the decoy receptor for IL-13, 34 and this expression represents an important tumor biomarker. In addition, recent studies of IL-13 reveal its central role in a novel immunoregulatory pathway in which natural killer T cells suppress tumor immunosurveillance.…”
Section: Introductionmentioning
confidence: 99%
“…For example, investigators showed that six of six pancreatic cancer cell lines examined expressed IL13Rα1 and IL4Rα, one cell line expressed IL13Rα2, and five pancreatic cancer cell lines expressed γc 10. IL13R-directed fusion toxins also have successfully been shown to kill pancreatic tumour cells 10 11…”
mentioning
confidence: 99%